10-Second heart rate variability and cognitive function in old age. (22nd March 2016) - Mahinrad, Simin; Jukema, J. Wouter; van Heemst, Diana; Macfarlane, Peter W.; Clark, Elaine N.; de Craen, Anton J.M.; Sabayan, Behnam
Abstract : Objective: To investigate the cross-sectional and longitudinal associations of 10-second heart rate variability (HRV) with various domains of cognitive function in older participants at risk of cardiovascular disease. Methods: We studied 3, 583 participants, mean age of 75.0 years, who were enrolled in the Prospective Study of Pravastatin in the Elderly at Risk. From baseline 10-second ECGs, standard deviation of normal-to-normal intervals was calculated as the index of HRV. Four cognitive domains were assessed at baseline and repeated during a mean follow-up period of 3.2 years. Results: Lower HRV at baseline was associated with worse performance in reaction time (mean difference between low third vs high third of HRV = 1.96 seconds, 95% confidence interval [CI] 0.20 to 3.71) and processing speed (−0.57 digits coded, 95% CI −1.09 to −0.05). During follow-up, participants with lower HRV had a steeper decline in processing speed (mean annual change between low third vs high third of HRV = −0.16 digits coded, 95% CI −0.28 to −0.04). There was no difference in annual changes of reaction time or immediate and delayed memory among HRV thirds during follow-up. All these associations remained unchanged after adjustment for medications, cardiovascular risk factors, and comorbidities. Conclusions: Participants with lower 10-second HRV have worse performance in reaction time and processing speed and experience steeper decline in their processing speed, independent of medications, cardiovascular risk factors, and comorbidities.